Hypocholesterolemic potential and bioactivity spectrum of an exopolysaccharide from a probiotic isolate Lactobacillus paracasei M7. (July 2019) - Bhat, Bilqeesa; Bajaj, Bijender Kumar
Abstract: Ever-rising prevalence of cardiovascular diseases (CVDs) has induced enormous research impetus for reducing cardiovascular risk factors through innovative approaches. One of the major causes of CVDs is elevated level of serum cholesterol which though could be managed by drugs. But considering serious side effects of most of the available cholesterol lowering drugs, development of nonpharmacological cholesterol lowering approaches have gained momentum. Probiotics and/or derived metabolites (such as exopolysaccharides) are reported for their ability to reduce serum cholesterol level. Exopolysaccharides (EPS) due to their wide bioactivity spectrum (hypocholesterolemic, antioxidant, immunostimulatory, and others), and usage as food-additive (thickener, stabilizer, gelling agent, and others) may have application potential for pharmaceutical/food industries. Current study reports the EPS producing potential of a probiotic Lactobacillus paracasei M7, an isolate from human breast milk. The EPS of L. paracasei M7 exhibited excellent functional characteristics like hypocholesterolemic (70.78%), antioxidant activity (DPPH radical scavenging activity 78.09%; hydroxyl radical scavenging activity 74.64%), and antibiofilm potential (59–64%) against several human pathogens. The EPS formed highly stable emulsion with vegetable oils (olive, peanut, coconut, and soybean oil). Although hypocholesterolemic activity of probiotics is known but scarce reports are available on cholesterol lowering potential of EPS. Physicochemical analysis of L. paracasei M7 EPS by FTIR, XRD, HPLC, SEM, and TEM, and thermal analysis (TGA/DSC) elucidated the structure-function relationship, and provided insights into the functional mechanisms of EPS. Versatile bioactivity potential of L. paracasei M7 EPS reflects its application prospective in food and pharmaceutical industry, especially for management of CVDs. Graphical abstract: Image 1